A practical perspective on One CGIAR: lessons from 15 years of CIALCA agricultural research for development consortium work in central Africa - Schut, Marc; Remans, R.; Birachi, Eliud Abucheli; Blomme, Guy; Craenen, K.; Delvaux, B.; Dercon, G.; Ekesa, B.; Kagabo, D.; Bacishoga, M.K.; Kantengwa, S.; Karangwa, P.; et al. (International Institute of Tropical Agriculture, 2021)
There is a wind of change blowing through the sector of international agricultural research for development (AR4D), mainly as a result of comprehensive reorganisation and transformation of one of its largest players, the CGIAR. In January 2020, Food Policy published a Special Issue providing valuable external and high-level reflections, challenges and recommendations for One CGIAR. One of the papers by Coffman et al. (2020) provided five Challenges and related Recommendations to the One CGIAR.